Influence of diabetes and other risk factors on in-hospital mortality following kidney transplantation: an analysis of the Spanish National Hospital Discharge Database from 2016 to 2020 - Javier de Miguel-Diez; Ana Lopez-de-Andres; Valentin Hernandez-Barrera; Marta Lopez-Herranz; Rodrigo Jimenez-Garcia; José Javier Zamorano-Leon; David Carabantes-Alarcon; Francisco Carricondo; Barbara Romero-Gomez; Natividad Cuadrado-Corrales (BMJ Open Diabetes Research & Care)
Introduction To assess time trends in incidence, clinical characteristics, complications, and hospital outcomes among patients with type 1 diabetes (T1D), with type 2 diabetes (T2D), and patients without diabetes who underwent kidney transplant (KT); to identify variables associated with in-hospital mortality (IHM); and to determine the impact of the COVID-19 pandemic.Research design and methods We used a nationwide discharge database to select KT recipients admitted to Spanish hospitals from 2016 to 2020. We stratified patients according to diabetes status. We used multivariable logistic regression to identify the variables associated with IHM.Results A total of 14 594 KTs were performed in Spain (T2D, 22.28%; T1D, 3.72%). The number of KTs rose between 2016 and 2019 and and decreased from 2019 to 2020 in all groups. In patients with T2D, the frequency of KT complications increased from 21.08% in 2016 to 34.17% in 2020 (p<0.001). Patients with T2D had significantly more comorbidity than patients with T1D and patients without diabetes (p<0.001). Patients with T1D experienced KT rejection significantly more frequently (8.09%) than patients with T2D (5.57%).COVID-19 was recorded in 26 out of the 2444 KTs performed in 2020, being found in 6 of the 39 patients deceased that year (15.38%) and in 0.83% of the survivors.The variables associated with IHM were comorbidity and complications of KT. The presence of T1D was associated with IHM (OR 2.6; 95% CI 1.36 to 5.16) when patients without diabetes were the reference category. However, T2D was not associated with a higher IHM (OR 0.86; 95% CI 0.61 to 1.2).Conclusions The COVID-19 pandemic led to a decrease in the number of transplants. Patients with T1D have more rejection of the transplanted organ than patients with T2D. Fewer women with T2D undergo KT. The presence of T1D is a risk factor for IHM.